Design and Development of Alumni Career Information System using PHP MySQL - Hamid, Mustofa Abi; Aribowo, Didik; Anggraini, Rini (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
Alumni data collection at the Electrical Engineering Vocational Education Universitas Sultan Ageng Tirtayasa was still performed manually and there were no career information media about soft skills training and development, tracer studies, and job vacancies information. Therefore, media is needed to accommodate career information and alumni data collection quickly and effectively. The web-based information system using PHP MySQL was developed and tested for feasibility as an information medium for soft skills training and development, tracer studies, job vacancies information, as well as career counseling and consulting. This study used a Modify R&D as a development method and the waterfall method as a development model consisted of analysis, design, coding (implementation), and testing. The testing was carried out by 37 people consisted of software experts, admins, alumni, and students of Electrical Engineering Vocational Education. The test was based on the ISO9126 standard with functionality, usability, reliability, and efficiency aspects. Based on the results, the functionality aspect had a score of 77 (very feasible), the usability aspect had a score of 87.8 (very feasible), the reliability aspect had a score of 100% (very feasible) and the average page load time was 3.48 seconds (feasible).